MAYBE Initial complexity problem: 1: T: (1, 1) f0(a, b) -> f2(c, d) [ c >= 1 /\ c >= 5 /\ c >= 2 /\ c >= 3 ] (1, 1) f0(a, b) -> f2(1, c) [ 0 >= 4 /\ 0 >= 1 ] (1, 1) f0(a, b) -> f2(c, d) [ c >= 1 /\ c >= 5 /\ 0 >= c /\ c >= 3 ] (1, 1) f0(a, b) -> f2(1, c) [ 0 >= 4 /\ 0 >= 1 ] (1, 1) f0(a, b) -> f2(3, c) (1, 1) f0(a, b) -> f2(1, c) [ 0 >= 1 ] (1, 1) f0(a, b) -> f2(3, c) [ 0 >= 3 ] (1, 1) f0(a, b) -> f2(1, c) [ 0 >= 1 ] (?, 1) f2(a, b) -> f2(b, c) [ b >= 5 /\ b >= 2 /\ b >= 3 /\ a = 2*b ] (?, 1) f2(a, b) -> f2(b, c) [ b >= 5 /\ b >= 2 /\ 1 >= b /\ a = 2*b ] (?, 1) f2(a, b) -> f2(b, c) [ b >= 5 /\ 0 >= b /\ b >= 3 /\ a = 2*b ] (?, 1) f2(a, b) -> f2(b, c) [ b >= 5 /\ 0 >= b /\ 1 >= b /\ a = 2*b ] (?, 1) f2(a, b) -> f2(b, c) [ b = 3 /\ a = 6 ] (?, 1) f2(a, b) -> f2(b, c) [ 3 >= b /\ b >= 2 /\ 1 >= b /\ a = 2*b ] (?, 1) f2(a, b) -> f2(b, c) [ 0 >= 3 /\ b = 3 /\ a = 6 ] (?, 1) f2(a, b) -> f2(b, c) [ 3 >= b /\ 0 >= b /\ 1 >= b /\ a = 2*b ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 0 >= 6*b + 3 /\ a = 2*b + 1 ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ 6*b >= 1 /\ 0 >= 6*b + 4 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ 6*b >= 1 /\ 0 >= 6*b + 4 /\ 0 >= 6*b + 3 /\ a = 2*b + 1 ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ 0 >= 6*b + 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ 0 >= 6*b + 1 /\ 6*b + 2 >= 0 /\ 0 >= 6*b + 3 /\ a = 2*b + 1 ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ 0 >= 6*b + 1 /\ 0 >= 6*b + 4 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ 0 >= 6*b + 1 /\ 0 >= 6*b + 4 /\ 0 >= 6*b + 3 /\ a = 2*b + 1 ] start location: f0 leaf cost: 0 Testing for unsatisfiable constraints removes the following transitions from problem 1: f0(a, b) -> f2(1, c) [ 0 >= 4 /\ 0 >= 1 ] f0(a, b) -> f2(c, d) [ c >= 1 /\ c >= 5 /\ 0 >= c /\ c >= 3 ] f0(a, b) -> f2(1, c) [ 0 >= 4 /\ 0 >= 1 ] f0(a, b) -> f2(1, c) [ 0 >= 1 ] f0(a, b) -> f2(3, c) [ 0 >= 3 ] f0(a, b) -> f2(1, c) [ 0 >= 1 ] f2(a, b) -> f2(b, c) [ b >= 5 /\ b >= 2 /\ 1 >= b /\ a = 2*b ] f2(a, b) -> f2(b, c) [ b >= 5 /\ 0 >= b /\ b >= 3 /\ a = 2*b ] f2(a, b) -> f2(b, c) [ b >= 5 /\ 0 >= b /\ 1 >= b /\ a = 2*b ] f2(a, b) -> f2(b, c) [ 3 >= b /\ b >= 2 /\ 1 >= b /\ a = 2*b ] f2(a, b) -> f2(b, c) [ 0 >= 3 /\ b = 3 /\ a = 6 ] f2(a, b) -> f2(6*b + 4, c) [ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 0 >= 6*b + 3 /\ a = 2*b + 1 ] f2(a, b) -> f2(6*b + 4, c) [ 6*b >= 1 /\ 0 >= 6*b + 4 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] f2(a, b) -> f2(6*b + 4, c) [ 6*b >= 1 /\ 0 >= 6*b + 4 /\ 0 >= 6*b + 3 /\ a = 2*b + 1 ] f2(a, b) -> f2(6*b + 4, c) [ 0 >= 6*b + 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] f2(a, b) -> f2(6*b + 4, c) [ 0 >= 6*b + 1 /\ 6*b + 2 >= 0 /\ 0 >= 6*b + 3 /\ a = 2*b + 1 ] f2(a, b) -> f2(6*b + 4, c) [ 0 >= 6*b + 1 /\ 0 >= 6*b + 4 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] We thus obtain the following problem: 2: T: (1, 1) f0(a, b) -> f2(c, d) [ c >= 1 /\ c >= 5 /\ c >= 2 /\ c >= 3 ] (1, 1) f0(a, b) -> f2(3, c) (?, 1) f2(a, b) -> f2(b, c) [ b >= 5 /\ b >= 2 /\ b >= 3 /\ a = 2*b ] (?, 1) f2(a, b) -> f2(b, c) [ b = 3 /\ a = 6 ] (?, 1) f2(a, b) -> f2(b, c) [ 3 >= b /\ 0 >= b /\ 1 >= b /\ a = 2*b ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ 0 >= 6*b + 1 /\ 0 >= 6*b + 4 /\ 0 >= 6*b + 3 /\ a = 2*b + 1 ] start location: f0 leaf cost: 0 Testing for reachability in the complexity graph removes the following transitions from problem 2: f2(a, b) -> f2(b, c) [ 3 >= b /\ 0 >= b /\ 1 >= b /\ a = 2*b ] f2(a, b) -> f2(6*b + 4, c) [ 0 >= 6*b + 1 /\ 0 >= 6*b + 4 /\ 0 >= 6*b + 3 /\ a = 2*b + 1 ] We thus obtain the following problem: 3: T: (?, 1) f2(a, b) -> f2(6*b + 4, c) [ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] (?, 1) f2(a, b) -> f2(b, c) [ b = 3 /\ a = 6 ] (?, 1) f2(a, b) -> f2(b, c) [ b >= 5 /\ b >= 2 /\ b >= 3 /\ a = 2*b ] (1, 1) f0(a, b) -> f2(3, c) (1, 1) f0(a, b) -> f2(c, d) [ c >= 1 /\ c >= 5 /\ c >= 2 /\ c >= 3 ] start location: f0 leaf cost: 0 Applied AI with 'oct' on problem 3 to obtain the following invariants: For symbol f2: X_1 - 3 >= 0 This yielded the following problem: 4: T: (1, 1) f0(a, b) -> f2(c, d) [ c >= 1 /\ c >= 5 /\ c >= 2 /\ c >= 3 ] (1, 1) f0(a, b) -> f2(3, c) (?, 1) f2(a, b) -> f2(b, c) [ a - 3 >= 0 /\ b >= 5 /\ b >= 2 /\ b >= 3 /\ a = 2*b ] (?, 1) f2(a, b) -> f2(b, c) [ a - 3 >= 0 /\ b = 3 /\ a = 6 ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ a - 3 >= 0 /\ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(3, c) with all transitions in problem 4, the following new transition is obtained: f0(a, b) -> f2(6*c + 4, c') [ 0 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ 3 = 2*c + 1 ] We thus obtain the following problem: 5: T: (1, 2) f0(a, b) -> f2(6*c + 4, c') [ 0 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ 3 = 2*c + 1 ] (1, 1) f0(a, b) -> f2(c, d) [ c >= 1 /\ c >= 5 /\ c >= 2 /\ c >= 3 ] (?, 1) f2(a, b) -> f2(b, c) [ a - 3 >= 0 /\ b >= 5 /\ b >= 2 /\ b >= 3 /\ a = 2*b ] (?, 1) f2(a, b) -> f2(b, c) [ a - 3 >= 0 /\ b = 3 /\ a = 6 ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ a - 3 >= 0 /\ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(6*c + 4, c') [ 0 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ 3 = 2*c + 1 ] with all transitions in problem 5, the following new transition is obtained: f0(a, b) -> f2(c', c'') [ 0 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ 3 = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' ] We thus obtain the following problem: 6: T: (1, 3) f0(a, b) -> f2(c', c'') [ 0 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ 3 = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' ] (1, 1) f0(a, b) -> f2(c, d) [ c >= 1 /\ c >= 5 /\ c >= 2 /\ c >= 3 ] (?, 1) f2(a, b) -> f2(b, c) [ a - 3 >= 0 /\ b >= 5 /\ b >= 2 /\ b >= 3 /\ a = 2*b ] (?, 1) f2(a, b) -> f2(b, c) [ a - 3 >= 0 /\ b = 3 /\ a = 6 ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ a - 3 >= 0 /\ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(c', c'') [ 0 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ 3 = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' ] with all transitions in problem 6, the following new transition is obtained: f0(a, b) -> f2(6*c'' + 4, c''') [ 0 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ 3 = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' /\ c' - 3 >= 0 /\ 6*c'' >= 1 /\ 6*c'' + 2 >= 0 /\ 6*c'' + 1 >= 0 /\ c' = 2*c'' + 1 ] We thus obtain the following problem: 7: T: (1, 4) f0(a, b) -> f2(6*c'' + 4, c''') [ 0 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ 3 = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' /\ c' - 3 >= 0 /\ 6*c'' >= 1 /\ 6*c'' + 2 >= 0 /\ 6*c'' + 1 >= 0 /\ c' = 2*c'' + 1 ] (1, 1) f0(a, b) -> f2(c, d) [ c >= 1 /\ c >= 5 /\ c >= 2 /\ c >= 3 ] (?, 1) f2(a, b) -> f2(b, c) [ a - 3 >= 0 /\ b >= 5 /\ b >= 2 /\ b >= 3 /\ a = 2*b ] (?, 1) f2(a, b) -> f2(b, c) [ a - 3 >= 0 /\ b = 3 /\ a = 6 ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ a - 3 >= 0 /\ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(6*c'' + 4, c''') [ 0 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ 3 = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' /\ c' - 3 >= 0 /\ 6*c'' >= 1 /\ 6*c'' + 2 >= 0 /\ 6*c'' + 1 >= 0 /\ c' = 2*c'' + 1 ] with all transitions in problem 7, the following new transition is obtained: f0(a, b) -> f2(c''', c'''') [ 0 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ 3 = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' /\ c' - 3 >= 0 /\ 6*c'' >= 1 /\ 6*c'' + 2 >= 0 /\ 6*c'' + 1 >= 0 /\ c' = 2*c'' + 1 /\ c''' >= 5 /\ c''' >= 2 /\ c''' >= 3 /\ 6*c'' + 4 = 2*c''' ] We thus obtain the following problem: 8: T: (1, 5) f0(a, b) -> f2(c''', c'''') [ 0 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ 3 = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' /\ c' - 3 >= 0 /\ 6*c'' >= 1 /\ 6*c'' + 2 >= 0 /\ 6*c'' + 1 >= 0 /\ c' = 2*c'' + 1 /\ c''' >= 5 /\ c''' >= 2 /\ c''' >= 3 /\ 6*c'' + 4 = 2*c''' ] (1, 1) f0(a, b) -> f2(c, d) [ c >= 1 /\ c >= 5 /\ c >= 2 /\ c >= 3 ] (?, 1) f2(a, b) -> f2(b, c) [ a - 3 >= 0 /\ b >= 5 /\ b >= 2 /\ b >= 3 /\ a = 2*b ] (?, 1) f2(a, b) -> f2(b, c) [ a - 3 >= 0 /\ b = 3 /\ a = 6 ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ a - 3 >= 0 /\ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] start location: f0 leaf cost: 0 By chaining the transition f2(a, b) -> f2(b, c) [ a - 3 >= 0 /\ b = 3 /\ a = 6 ] with all transitions in problem 8, the following new transition is obtained: f2(a, b) -> f2(6*c + 4, c') [ a - 3 >= 0 /\ b = 3 /\ a = 6 /\ b - 3 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ b = 2*c + 1 ] We thus obtain the following problem: 9: T: (?, 2) f2(a, b) -> f2(6*c + 4, c') [ a - 3 >= 0 /\ b = 3 /\ a = 6 /\ b - 3 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ b = 2*c + 1 ] (1, 5) f0(a, b) -> f2(c''', c'''') [ 0 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ 3 = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' /\ c' - 3 >= 0 /\ 6*c'' >= 1 /\ 6*c'' + 2 >= 0 /\ 6*c'' + 1 >= 0 /\ c' = 2*c'' + 1 /\ c''' >= 5 /\ c''' >= 2 /\ c''' >= 3 /\ 6*c'' + 4 = 2*c''' ] (1, 1) f0(a, b) -> f2(c, d) [ c >= 1 /\ c >= 5 /\ c >= 2 /\ c >= 3 ] (?, 1) f2(a, b) -> f2(b, c) [ a - 3 >= 0 /\ b >= 5 /\ b >= 2 /\ b >= 3 /\ a = 2*b ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ a - 3 >= 0 /\ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] start location: f0 leaf cost: 0 By chaining the transition f2(a, b) -> f2(6*c + 4, c') [ a - 3 >= 0 /\ b = 3 /\ a = 6 /\ b - 3 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ b = 2*c + 1 ] with all transitions in problem 9, the following new transition is obtained: f2(a, b) -> f2(c', c'') [ a - 3 >= 0 /\ b = 3 /\ a = 6 /\ b - 3 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ b = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' ] We thus obtain the following problem: 10: T: (?, 3) f2(a, b) -> f2(c', c'') [ a - 3 >= 0 /\ b = 3 /\ a = 6 /\ b - 3 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ b = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' ] (1, 5) f0(a, b) -> f2(c''', c'''') [ 0 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ 3 = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' /\ c' - 3 >= 0 /\ 6*c'' >= 1 /\ 6*c'' + 2 >= 0 /\ 6*c'' + 1 >= 0 /\ c' = 2*c'' + 1 /\ c''' >= 5 /\ c''' >= 2 /\ c''' >= 3 /\ 6*c'' + 4 = 2*c''' ] (1, 1) f0(a, b) -> f2(c, d) [ c >= 1 /\ c >= 5 /\ c >= 2 /\ c >= 3 ] (?, 1) f2(a, b) -> f2(b, c) [ a - 3 >= 0 /\ b >= 5 /\ b >= 2 /\ b >= 3 /\ a = 2*b ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ a - 3 >= 0 /\ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] start location: f0 leaf cost: 0 By chaining the transition f2(a, b) -> f2(c', c'') [ a - 3 >= 0 /\ b = 3 /\ a = 6 /\ b - 3 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ b = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' ] with all transitions in problem 10, the following new transition is obtained: f2(a, b) -> f2(6*c'' + 4, c''') [ a - 3 >= 0 /\ b = 3 /\ a = 6 /\ b - 3 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ b = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' /\ c' - 3 >= 0 /\ 6*c'' >= 1 /\ 6*c'' + 2 >= 0 /\ 6*c'' + 1 >= 0 /\ c' = 2*c'' + 1 ] We thus obtain the following problem: 11: T: (?, 4) f2(a, b) -> f2(6*c'' + 4, c''') [ a - 3 >= 0 /\ b = 3 /\ a = 6 /\ b - 3 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ b = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' /\ c' - 3 >= 0 /\ 6*c'' >= 1 /\ 6*c'' + 2 >= 0 /\ 6*c'' + 1 >= 0 /\ c' = 2*c'' + 1 ] (1, 5) f0(a, b) -> f2(c''', c'''') [ 0 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ 3 = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' /\ c' - 3 >= 0 /\ 6*c'' >= 1 /\ 6*c'' + 2 >= 0 /\ 6*c'' + 1 >= 0 /\ c' = 2*c'' + 1 /\ c''' >= 5 /\ c''' >= 2 /\ c''' >= 3 /\ 6*c'' + 4 = 2*c''' ] (1, 1) f0(a, b) -> f2(c, d) [ c >= 1 /\ c >= 5 /\ c >= 2 /\ c >= 3 ] (?, 1) f2(a, b) -> f2(b, c) [ a - 3 >= 0 /\ b >= 5 /\ b >= 2 /\ b >= 3 /\ a = 2*b ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ a - 3 >= 0 /\ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] start location: f0 leaf cost: 0 By chaining the transition f2(a, b) -> f2(6*c'' + 4, c''') [ a - 3 >= 0 /\ b = 3 /\ a = 6 /\ b - 3 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ b = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' /\ c' - 3 >= 0 /\ 6*c'' >= 1 /\ 6*c'' + 2 >= 0 /\ 6*c'' + 1 >= 0 /\ c' = 2*c'' + 1 ] with all transitions in problem 11, the following new transition is obtained: f2(a, b) -> f2(c''', c'''') [ a - 3 >= 0 /\ b = 3 /\ a = 6 /\ b - 3 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ b = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' /\ c' - 3 >= 0 /\ 6*c'' >= 1 /\ 6*c'' + 2 >= 0 /\ 6*c'' + 1 >= 0 /\ c' = 2*c'' + 1 /\ c''' >= 5 /\ c''' >= 2 /\ c''' >= 3 /\ 6*c'' + 4 = 2*c''' ] We thus obtain the following problem: 12: T: (?, 5) f2(a, b) -> f2(c''', c'''') [ a - 3 >= 0 /\ b = 3 /\ a = 6 /\ b - 3 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ b = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' /\ c' - 3 >= 0 /\ 6*c'' >= 1 /\ 6*c'' + 2 >= 0 /\ 6*c'' + 1 >= 0 /\ c' = 2*c'' + 1 /\ c''' >= 5 /\ c''' >= 2 /\ c''' >= 3 /\ 6*c'' + 4 = 2*c''' ] (1, 5) f0(a, b) -> f2(c''', c'''') [ 0 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ 3 = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' /\ c' - 3 >= 0 /\ 6*c'' >= 1 /\ 6*c'' + 2 >= 0 /\ 6*c'' + 1 >= 0 /\ c' = 2*c'' + 1 /\ c''' >= 5 /\ c''' >= 2 /\ c''' >= 3 /\ 6*c'' + 4 = 2*c''' ] (1, 1) f0(a, b) -> f2(c, d) [ c >= 1 /\ c >= 5 /\ c >= 2 /\ c >= 3 ] (?, 1) f2(a, b) -> f2(b, c) [ a - 3 >= 0 /\ b >= 5 /\ b >= 2 /\ b >= 3 /\ a = 2*b ] (?, 1) f2(a, b) -> f2(6*b + 4, c) [ a - 3 >= 0 /\ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] start location: f0 leaf cost: 0 By chaining the transition f2(a, b) -> f2(6*b + 4, c) [ a - 3 >= 0 /\ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 ] with all transitions in problem 12, the following new transition is obtained: f2(a, b) -> f2(c, c') [ a - 3 >= 0 /\ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 /\ c >= 5 /\ c >= 2 /\ c >= 3 /\ 6*b + 4 = 2*c ] We thus obtain the following problem: 13: T: (?, 2) f2(a, b) -> f2(c, c') [ a - 3 >= 0 /\ 6*b >= 1 /\ 6*b + 2 >= 0 /\ 6*b + 1 >= 0 /\ a = 2*b + 1 /\ c >= 5 /\ c >= 2 /\ c >= 3 /\ 6*b + 4 = 2*c ] (?, 5) f2(a, b) -> f2(c''', c'''') [ a - 3 >= 0 /\ b = 3 /\ a = 6 /\ b - 3 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ b = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' /\ c' - 3 >= 0 /\ 6*c'' >= 1 /\ 6*c'' + 2 >= 0 /\ 6*c'' + 1 >= 0 /\ c' = 2*c'' + 1 /\ c''' >= 5 /\ c''' >= 2 /\ c''' >= 3 /\ 6*c'' + 4 = 2*c''' ] (1, 5) f0(a, b) -> f2(c''', c'''') [ 0 >= 0 /\ 6*c >= 1 /\ 6*c + 2 >= 0 /\ 6*c + 1 >= 0 /\ 3 = 2*c + 1 /\ c' >= 5 /\ c' >= 2 /\ c' >= 3 /\ 6*c + 4 = 2*c' /\ c' - 3 >= 0 /\ 6*c'' >= 1 /\ 6*c'' + 2 >= 0 /\ 6*c'' + 1 >= 0 /\ c' = 2*c'' + 1 /\ c''' >= 5 /\ c''' >= 2 /\ c''' >= 3 /\ 6*c'' + 4 = 2*c''' ] (1, 1) f0(a, b) -> f2(c, d) [ c >= 1 /\ c >= 5 /\ c >= 2 /\ c >= 3 ] (?, 1) f2(a, b) -> f2(b, c) [ a - 3 >= 0 /\ b >= 5 /\ b >= 2 /\ b >= 3 /\ a = 2*b ] start location: f0 leaf cost: 0 Complexity upper bound ? Time: 2.307 sec (SMT: 2.168 sec)